Optical Properties of Polypropylene upon Recycling - Felice De Santis; Roberto Pantani (The Scientific World Journal)
In the last few years there has been an increasing interest in the possibility of recycling polymeric materials, using physical recycling. However, is it well known that polymers experience a depletion of all the properties upon recycling. These effects have been widely characterized in the literature for what concerns the mechanical or rheological properties. The changes of optical properties after recycling have been much less studied, even if, especially in food packaging, optical characteristics (above all the opacity) are of extreme importance, and thus it is quite significant to assess the effect of recycling on these properties. In this work, the influence of recycling steps on the opacity of films of a commercial grade of isotactic polypropylene (i-PP) was studied. The material was extruded several times to mimic the effect of recycling procedures. After extrusion, films were obtained by cooling samples of material at different cooling rates. The opacity of the obtained films was then measured and related to their crystallinity and morphology. It was found that opacity generally increases on increasing the amount of α phase and for the same amount of α phase on increasing the size of the spherulites.